The Future of Junior High School Citizenship Education in Indonesia: A SWOT Analysis - Annas Waladul Mufid, M. Khoirul; Turhan Yani, Muhammad; Harmanto; Suprijono, Agus (Jurnal PAJAR (Pendidikan dan Pengajaran), 2024)
Citizenship is an issue that will remain as long as there is an institution called the state. Therefore, citizenship problems will always exist as long as the concept of the state still exists. Citizenship Education (PKn) is one way to overcome or reduce citizenship problems. So, junior high schools (SMP) make citizenship a mandatory curriculum content. This research aims to analyze current Civics and future Civics using SWOT analysis. For this reason, a qualitative approach was used with the literature review method. As a result, 23 studies based on the criteria were selected as data sources. Several themes emerge regarding Civics currently, namely 1) citizenship education in a Merdeka curriculum, 2) problems of citizenship education, and 3) solutions to problems of citizenship education. Meanwhile, the subject of citizenship education will be discussed in the future. However, although it has advantages and opportunities, it still has shortcomings and challenges ranging from less interesting learning, lack of teacher competence, current developments, radicalism, even misinformation (hoaxes), shortcomings, opportunities, and challenges in teaching citizenship to middle school students. Therefore, there is a need for tactical strategies to optimize opportunities and reduce obstacles and challenges for civics at the junior high school level.